Use of Social Media for Effective Library and Information Services among University Students: A Study - Das, Arijit; Sarkar, Arindam (Journal of Information and Knowledge, 2021)
Information communication technology (ICT) plays a key role in the transmission of information between each other. Social networking sites are good examples of a network of communication and it is a good social structural way that allows the user to interact and work with other users. WhatsApp and Facebook are two very popular social media that very much help users to interact each other via text, image, audio, video messaging. This paper was based on a survey that measured the usability of Facebook and WhatsApp for service delivery to the library. An online questionnaire was used to collect information from the respondents. The findings indicated that respondents showed a positive attitude towards the services of library through Facebook and WhatsApp.